2009
DOI: 10.1051/dst/2009048
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition of yak milk

Abstract: -The protein composition of 24 individual Maiwa yak milk samples that were collected in the Sichuan province of China was determined by reversed-phase high-performance liquid chromatography. Yak milk differed from cow milk by its high concentration of total proteins (46.2-58.4 g·L −1 ), total casein (40.2 g·L −1 on average) and the proportion of individual caseins. The high content of β-casein (more than 45%) and consequently the lower proportion of α s -casein (about 40%) together with a small increase in κ-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 11 publications
(13 reference statements)
5
51
0
Order By: Relevance
“…Yak milk has greater contents of total proteins (4.6% -5.8%), total casein (4.0%) and individual caseins than cow milk. The higher β-casein (45%) and the lower α-s-casein (40%) along with somewhat higher κ-casein (15%) make yak milk a favorable food for infants as traditionally consumed by Tibetan nomads [37]. Yak milk's whey proteins, β-lactoglobulin and serum albumin compositions are rather similar to homologous cow whey proteins.…”
Section: Yak Milk For Nutrition and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Yak milk has greater contents of total proteins (4.6% -5.8%), total casein (4.0%) and individual caseins than cow milk. The higher β-casein (45%) and the lower α-s-casein (40%) along with somewhat higher κ-casein (15%) make yak milk a favorable food for infants as traditionally consumed by Tibetan nomads [37]. Yak milk's whey proteins, β-lactoglobulin and serum albumin compositions are rather similar to homologous cow whey proteins.…”
Section: Yak Milk For Nutrition and Healthmentioning
confidence: 99%
“…Along with high proteins, yak milk has high acidity. Saturated and unsaturated FA comprise respectively 22% and 55.2% of total fat, with greater content of low molecular weight volatile acids, compared to cow milk [37]. Mongolians produce from yak milk butter as well as fermented and protein products.…”
Section: Yak Milk For Nutrition and Healthmentioning
confidence: 99%
“…China is the largest producer of yaks in the world, with approximately 14.7 million, constituting to more than 95% of world yaks with annual yield of about 70,000 tonnes of milk (Zhong et al 2006). However, the yield of yak milk is low ranging from 147 to 487 kg per lactation period, compared to cow's milk, yak milk contains high content of proteins (4.9 -5.3%), total solids (16.9 -17.7%), fat (5.5 -7.2%), lactose (4.5 -5.0%) and minerals (0.8 -0.9%) (Dong et al 2007;Li et al 2010;Nikkhah, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It was showed that yak milk has a high concentration of total proteins (46.2-58.4 g.L −1 ) and total caseins (40.2 g.L −1 ) (Li et al 2010). The high content of β-casein (more than 45%) and consequently the lower proportion of αs-casein (about 40%) together with the high content of κ-casein (15%) in yak milk make it with a good proportion of individual caseins, which is similar to the proportion found in human milk and more favorable for infant nutrition (Li et al 2010). It also found the high content of minerals and micellar size of yak milk (Wang et al 2013;Yang et al 2014b).…”
Section: Introductionmentioning
confidence: 99%